Resource integration for livelihood and nutritional security of farmers of Tehri Himalayas of India - KASHYAP, POONAM; SINGH, M P; SINGH, V K; PRUSTY, A K; MISHRA, R P; CHAUDHARY, V P; GANGWAR, B (The Indian Journal of Agricultural Sciences, 2017)
Farming system approach is considered as most powerful tool for improving livelihood of small and marginal farmers. A study was undertaken during 2011-2015 to characterize the existing farming situation in New Tehri district of Uttarakhand with the objective of holistic improvement of livelihood, profit maximization and on-farm employment generation through integrated farming system (IFS) approach. Analysis of results revealed that crop + dairy was the predominant farming system (68%) followed by crop + dairy + horticulture + goatery. Introduction of improved cultivars of rice, maize, wheat and barley gave additional yield of 17 to 42 % over traditional cultivars. Similarly, introduction of improved cultivars and need based integrated pest management resulted in increased productivity of pre-dominant pulses like pigeonpea, blackgram, mungbean, kidneybean, horsegram, chickpea and lentil by 31% to 70%. Introduction of improved cultivars of soybean (Cv. PS 1092) and mustard (Cv. Pusa Bold) along with integrated plant nutrient management (IPNM) measures provided enhanced yield of 27% (soybean) and 46% (mustard) in Narendra Nagar, whereas yield enhancement of 15% (soybean) and 47% (mustard) was recorded in Thauldar Block. Interventions in horticulture component also resulted in yield improvement and enhanced productivity. The monthly vegetable availability increased from 110 to 154 kg house hold in the study area. The results of the study showed that annual requirement of proteins (110-125 kg) and carbohydrates (550 to 575 kg) for a five member can be easily met out through integrated farming system approach. This study envisaged that integrated farming system approach along with improved technological interventions may bring long-term farming system sustainability, improved livelihood and generate sufficient local employment which will restrict rural youth migration in hill areas of Uttarakhand.